Implikasi Hukum warisan hutang oleh warga negara asing dalam sengketa kepailitan di indonesia perspektif Lex Loci Dan Lex Poli - Nurfauzi Muhammad (Universitas Sains dan Teknologi Komputer, 2025)
Economic globalization has created legal complexities in cross-border bankruptcy disputes, particularly when involving foreign nationals who inherit debts. This study analyzes the application of the lex loci and lex fori principles in bankruptcy cases related to the inheritance of debts by foreign nationals in Indonesia, using the case study of PT. Krama Yudha. The research employs a normative-juridical approach with descriptive-analytical analysis of the Central Jakarta District Court Decision No. 226/Pdt.Sus-PKPU/2023 and the Supreme Court Decision No. 1103 K/PdtSus-Pailit/2024. The findings reveal inconsistencies in the application of private international law principles concerning the jurisdiction and liability of foreign heirs for the deceased’s debts. The lex loci principle provides protection for domestic creditors by subjecting assets located in Indonesia to national law, while lex fori emphasizes the application of Indonesian procedural law. However, the conflict between these principles creates legal uncertainty and disparities in protection for both creditors and heirs. This study recommends the harmonization of cross-border inheritance and bankruptcy laws, the adoption of the UNCITRAL Model Law on Cross-Border Insolvency, and the inclusion of clearer lex successionis provisions in the revision of the Bankruptcy Law to ensure justice and legal certainty.